Máquinas, corpo sem órgãos e pulsões: um diálogo entre O Anti-Edipo de Deleuze e Guattari e a metapsicologia freudiana - Sanches, Aline (2008)
In Anti-Oedipus (1972), Deleuze and Guattari make original critical analyses of psychoanalysis, and offer theoretical and practical proposals for the problems they identify in the Freudian legacy. However, the aggressive written and the peculiar style of this venture do not attract the readers interested in psychoanalysis, and this polemical book is commonly confused with a project of destruction and overcoming of psychoanalysis. The result is that, so far, it is still not clear whether - or how - the conceptual formulation developed by these authors can offer contributions to the psychoanalytic field, and few is discussed about the importance and relevance of this critical proposal. The dialogue between this work and psychoanalysis is usually exempted, unless when you intend to reaffirm their opposition. It occurs that Anti-Oedipus maintains an ambiguous relationship with psychoanalysis, in that it does not cease to rely on central aspects of Freudian thought in its proposal to overcome the limitations and anachronisms of psychoanalysis. Indeed, the authors seek to devise an immanent and productive unconscious which is inconsistent with too expensive notions of psychoanalysis. On the other hand, the economic register of the Freudian unconscious is highly valued in this project, and the concepts of desiring-machine and body without organs, for example, are curiously articulated with the drives theory. Therefore, in this dissertation, we sought to present Anti-Oedipus considering that the authors also worked with the psychoanalysis, from a positive and specific resumption of the Freudian drives theory. Initially, we present this work through the concepts of desiring-machine and body without organs, advancing in their specific theses and identifying the assumptions involved in its construction. Then, we made some joints between these concepts and the Freud s drives theory, not suggesting that they are similar, but identifying the imposed questions to psychoanalysis from indications of Deleuze and Guattari. After this, it was found that these authors held a reading of the drives theory to compose the concepts of Anti-Oedipus, which is inseparable from a singular theoretical construction, where other problems and issues are being placed. We saw that his concept about the unconscious really goes beyond psychoanalysis, not because the beats, but because it is not limited to addressing psychoanalytical issues, much less is based only on freudian written to be forged. Thus, less than an iconoclast work, Anti-Oedipus emerges as a legitimate and vigorous enterprise in its investigation of the unconscious and the desire, where it is used to recommence alternatives lines witch born of psychoanalysis itself, through a complex preparation. The joints that we indicate and begin to explore here, are recognized as new possibilities of the reading of psychoanalysis, without, however, being reduced to this, but considered from its specific position.